REGULATIONS OF ELECTRICITY SECTOR AND STRANDED COSTS: CASE OF TURKEY - Ege, Ilhan (Journal of Advanced Research in Law and Economics; Vol 1 No 2 (2010): JARLE volume 1 Issue 2(2) Winter 2010, 2017)
Globalisation is the political phenomenon that has come to dominate the world since the nineties of the last century with the end of the cold war. It is been lowered the barriers to competition and investment. Energy sector liberalization is milestone in Turkey electricity market. Measurement of and finance to stranded costs of electricity sector are main problems of this liberalization. The main aim of this paper is analyzing Turkey electricity market liberalization and stranded costs.
Keywords: regulations, investment, electricity sector, stranded costs